Studies on Morphological and Seed Quality Parameters in Buckwheat (Fagopyrum esculentum Moench) Germplasm - Bisht, Anjay Singh; Bhatt, Arun; Jyoti, Bhim; Singh, Piyusha (International Journal of Bio-resource and Stress Management, 2018)
The present investigation was carried out during kharif season 2013 at the Research Block, Department of Crop Improvement for field experiment and further subsequent seed quality parameters were assessed in Seed Testing Laboratory for thirty diverse germplasm line of buckwheat including four check varieties i.e. PRB-1, Himpriya, VL-7 and Shimla-B1. Maintenance of morphological parameters, seed viability and vigour is crucial for success of any crop production programme as the sowing of deteriorated seed leads to sub optimal plant stand and crop performance. Among all the germplasm earliest flowering was noticed in RSR/SKS-106 (43 days) and day to maturity was noticed in IC-412733 (111 days). The maximum plant height (121.06 cm) was observed in PRB-1. Maximum number of primary branches per plant was recorded for PRB-1 (4.13) and VL-7 showed highest number of internodes plant-1 (12.86). PRB-1 (29.40) has highest number of leaves per plant while, PRB-1 was the best germplasm for highest seed yield plant-1 (3.45 g). The significantly highest germination percent was recorded for VL-7 (95%), while the minimum percent of standard germination was observed for IC-36805 (72%). The largest seedling length was measured for VL-7 (20.34 cm). The significantly maximum value of vigour index-I was observed for VL-7 (1900) germplasm. It is significant to mention that results of present study have helped to select better germplasm on the basis of morphological parameters and seed quality parameters in buckwheat. Out of 30 germplasm VL-7, PRB-1, IC-36805, IC-107988 and IC-26599 can be further utilized in crop improvement programme which is suitable for mid hills of Uttarakhand.